Syariah Courts' Practice on Declaring the Religious Status in the Case of Application to Renounce Islam: A Case Study in Negeri Sembilan Syariah High Court - Md Nasir, Nor Ashikin; Ismail, Siti Zubaidah (Kanun: Jurnal Undang-undang Malaysia; Vol 29 No 1 (2017): KANUN: Jurnal Undang-undang Malaysia Volume 29 Number 1 January 2017, 2017)
This article analyses the practice of the Syariah High Court of Negeri Sembilan in the case of applications to renounce Islam. This study examines the legal provision pertaining to leave Islam, section 119 of Negeri Sembilan's Enactment of Administration of Islamic Law, 2003 and the 45 case files registered in the High Court between 2003 and 2014. Analysis was carried out on selected themes such as the status of applicants, reasons for application, and the outcome of the court hearing. A semi-structured interview with the Mufti of Negeri Sembilan and the Officer in-charge of the Akidah Counselling Unit under the Mufti Department were conducted to observe the counselling processes. The study shows that section 119 of the Enactment is the legal instrument that guides the Syariah court in its judgment on pronouncing the status of the applicant, through section 61(3)(b)(ix) provided that the applicant has a reasonable cause to leave Islam and supported with strong evidence that is accepted by the court. In other words, with the amendment made to section 119 in 2009, there is more scrutiny and limits to renounce the religion. Keywords: leave Islam, Shariah High Court Negeri Sembilan, Islamic law